Six weeks of aerobic dance exercise improves blood oxidative stress status and increases interleukin-2 in previously sedentary women - Donrawee Leelarungrayub (2018)
This study evaluated the change in blood oxidative stress, blood interleukin-2, and physical performance following 6weeks of moderate intensity and duration aerobic dance exercise in 24 sedentary women. Blood samples were collected at rest twice before (baseline) and after the 6-week intervention for analysis of protein hydroperoxide (PrOOH), malondialdehyde (MDA), total anti-oxidant capacity (TAC), and interleukin-2 (IL-2) levels. Maximal treadmill run time (Timemax) and maximal oxygen consumption (VO2max) were also measured. All variables were statistically analyzed with a repeated measurement ANOVA and Tukey post hoc. No differences were noted in any variable during the baseline period (p > 0.05). After aerobic dance exercise, VO2max, Timemax, TAC and IL-2 were significantly increased, whereas MDA levels were decreased significantly (p < 0.05). PrOOH did not change either between baseline measures or after exercise. It can be concluded that aerobic dance exercise at a moderate intensity and duration can improve physical fitness, decrease MDA, and increase TAC and IL-2 in previously sedentary women. © 2010 Elsevier Ltd.